The Prospective Antifungal Therapy Alliance® Registry: A Two-Centre Canadian Experience. Issue 1 (2014) - Haider, Shariq; Rotstein, Coleman; Horn, David; Laverdiere, Michel; Azie, Nkechi
Abstract : BACKGROUND: The Prospective Antifungal Therapy Alliance ® registry is a prospective surveillance study that collected data on the diagnosis, management and outcomes of invasive fungal infections (IFIs) from 25 centres in North America from 2004 to 2008. OBJECTIVE: To evaluate surveillance data on IFIs obtained from study centres located in Canada. METHODS: Patients with proven or probable IFIs at two Canadian medical centres were enrolled in the registry. Information regarding patient demographics, fungal species, infection sites, diagnosis techniques, therapy and survival were analyzed. RESULTS: A total of 347 patients from Canada with documented IFIs were enrolled in the Prospective Antifungal Therapy Alliance registry. Infections occurred most commonly in general medicine (71.8%), nontransplant surgery (32.6%) and patients with hematological malignancies (21.0%). There were 287 proven IFIs, including 248 Candida infections. Forty-six patients had invasive aspergillosis (IA); all of these were probable infections. Most cases of invasive candidiasis were confirmed using blood culture (90.5%), while IA was most frequently diagnosed using computed tomography scan (82.6%) and serological methods (82.6%). Fluconazole was the most common therapy used for Candida infections, followed by the echinocandins. Voriconazole therapy was most commonly prescribed for IA. CONCLUSIONS: The present study demonstrated that general medicine, surgery and hematological malignancy patients in Canada are susceptible to developing IFIs. In contrast to the United States, Candida albicans remains responsible for most IFIs in these Canadian centres. Surrogate serum markers are commonly being used for the diagnosis of IA, while therapy for both IFIs has shifted to broader-spectrum azoles and echinocandins.